Mooring Lines Reliability Analysis Case Study: Fso Abherka - Garry Raditya Putra; Daniel Mohammad Rosyid; Rudi Walujo Prastianto (IPTEK The Journal for Technology and Science, 2021)
Floating Storage and Offloading (FSO) demands good designs. One of the design is FSO’s mooring lines. The mooring lines of the FSO would face various environmental conditions, so that they are required to have good reliability. FSO Abherka, installed in the Madura stratit, has dimensions of LOA 242.90 m, LPP 232 m, Breadth 41.6 m, Height 19.7 m, Draft 12,894 m, and a deadweight of 85829 tons. The strait has a water depth of 100 m with contour variations of ± 2 m. Each four cluster of mooring lines of FSO Abherka has three mooring ropes. This study analyzed the strength of mooring lines in intact and damaged conditions using DNV software Genie and DNV HydroD. This study models a hydrodynamic FSO. This study also measured the reliability of the mooring lines from 2 cases: 1 intact and one damage from the most dangerous conditions. This study used the mean Value First Order Second Moment method to find the reliability of these mooring lines. Based on the reliability calculation set by DNV according to DNV-OS E301, the mooring lines design meet the established reliability criteria